Postural deformities in patients with Parkinson disease (clinical and social aspects) - I. V. Fursova; V. A. Mikhailov; D. V. Zakharov; A. P. Kovalenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
The analysis was presentedabout the dynamics of the functional and psychological state and quality of life of patients with trunk deformities in Parkinson’s diseaseusing Dysport. The optimal regimens was reflected about the administration of botulinum toxin for patients with camptocormia and Pisa syndrome.